Follicle-Stimulating Hormone Receptor Expression in Endometriotic Lesions and the Associated Vasculature: An Immunohistochemical Study. (July 2016) - Robin, Blaise; Planeix, François; Sastre-Garau, Xavier; Pichon, Christophe; Olesen, Tine Kold; Gogusev, Jean; Ghinea, Nicolae
Follicle-stimulating hormone receptor (FSHR) is present on endothelial cells of blood vessels and endometrial glands of the proliferative and secretory endometrium. So far, the expression of FSHR in endometriosis has not been studied. We evaluated FSHR expression in 194 tissue specimens representing 3 relevant types of endometriosis: rectovaginal endometriotic nodules, ovarian endometriotic cysts, and peritoneal endometriotic implants. Specimens of normal endometrium were used as controls. Archival formalin-fixed and paraffin-embedded material was analyzed immunohistochemically with a highly specific monoclonal antihuman FSHR antibody using the peroxidase method. A robust vascular FSHR expression was found in all 194 patients, irrespective of the endometriosis lesion location. Follicle-stimulating hormone receptor was not detected in normal host tissues located more than 5 mm from the lesions. The endometriotic lymphatic vessels do not express FSHR. The density of FSHR-positive vessels in patients with rectovaginal endometriotic nodules was 46.0 ± 5.7 vessels/mm 2 . Similar values were obtained for ovarian endometriotic cysts and peritoneal endometriosis. The density of FSHR-positive vessels associated with the core of rectovaginal endometriotic nodules was 2-fold higher than that of the perilesional, adjacent normal host tissue (64.2 ± 8.2 vs 27.2 ± 3.2 vessels/mm 2, respectively). Expression of FSHR was also detected either in endometriotic glandular epithelial cells, endometriotic stromal cells, or in both cell types (23%, 25%, and 21% of patients, respectively). Normal endometrium expressed FSHR predominately in basalis, in a cellular distribution dependent on hormonal environment. In conclusion, our data suggest novel FSHR expression in endometriotic lesions, qualitatively and quantitatively different from that of normal endometrium.